Skin permeability, a dismissed necessity for anti‐wrinkle peptide performance - Mortazavi, Seyedeh Maryam; Moghimi, Hamid Reza (International journal of cosmetic science, 2022)
Background The skin offers various benefits and potential for peptide delivery if its barrier performance can be reduced temporarily and reversibly. As peptides possess high molecular weight, hydrophilic nature (in most cases), and ionizable groups in the structure, their skin delivery is highly challenging. Apart from this, they are susceptible to the proteolytic enzymes in the skin. Anti‐wrinkle peptides, like other peptides, suffer from insufficient skin permeability, while most of them must penetrate deep in the skin to present their efficacy. Although the cellular studies indicate the effectiveness of such peptides, without the ability to permeate the skin sufficiently, this efficacy is useless. Poor skin permeability of anti‐wrinkle peptides has led to ongoing research for finding feasible and noninvasive enhancement methods that would be desirable for consumers of cosmetic products. Method In this paper, the possibility of skin permeation of anti‐wrinkle peptides as well as the chemical, physical, and encapsulation approaches that have been employed to date to increase permeability of these difficult molecules are thoroughly reviewed. Results Most anti‐wrinkle peptides are not appropriate candidates for skin permeation and the use of enhancement methods is essential to increase their permeability. To do so, only some permeability enhancement approaches have been applied so far, including chemical modification with hydrophobic moieties or cell penetrating peptides, metal complexation, chemical permeation enhancers, iontophoresis, microneedles, and encapsulation in nanocarriers. The results of studies published on the skin permeability of anti‐wrinkle peptides carnosine, GHK, PKEK, GEKG, GQPR, and KTTKS indicate that the skin permeability of these peptides can be successfully increased. Conclusion Although the skin permeability of most anti‐wrinkle peptides is not high enough and most anti‐wrinkle peptides might not reach their targets in the skin at right concentrations, their permeability can be increased to therapeutic concentrations using various enhancement approaches. Résumé Contexte La peau offre divers avantages et a la faculté de recevoir des peptides si l’on parvient à réduire temporairement et de manière réversible sa capacité à fonctionner comme une barrière. Comme les peptides ont un poids moléculaire élevé, une nature hydrophile (dans la plupart des cas) et possèdent des groupes ionisables dans leur structure, il est très difficile d’en faire bénéficier la peau. En outre, ils sont sensibles aux enzymes protéolytiques de la peau. Les peptides antirides, comme d’autres peptides, souffrent d’une capacité insuffisante de perméation de la peau ; or, la plupart d’entre eux doivent y pénétrer profondément pour avoir une efficacité. Bien que les études cellulaires indiquent l’efficacité de ces peptides, s’ils sont incapables de pénétrer suffisamment la peau, cette efficacité est inopérante. Face à cette perméabilité médiocre de la peau aux peptides antirides, des recherches sont menées actuellement pour trouver des méthodes d’amélioration à la fois réalisables et non invasives, qui soient attractives pour les consommateurs de produits cosmétiques. Méthode Dans cet article, nous étudions de manière approfondie la possibilité de perméation des peptides antirides à travers l’épiderme, ainsi que les approches chimiques, physiques et d’encapsulation utilisées à ce jour pour augmenter l’aptitude à la perméation de ces molécules difficiles. Résultats La plupart des peptides antirides ne sont pas de bons candidats à la perméation de l’épiderme, et il est essentiel d’avoir recours à des méthodes de renforcement pour augmenter leur capacité de pénétration. Pour ce faire, seules certaines approches de renforcement de la perméation ont été appliquées jusqu’à présent : une modification chimique avec des fractions hydrophobes ou des peptides pénétrants la cellule ; la complexation métallique ; les amplificateurs de perméation chimique ; l’iontophorèse ; les micro‐aiguilles et l’encapsulation dans les nano supports. Les résultats des études publiées sur la perméabilité de l’épiderme aux peptides antirides que sont la carnosine, le GHK, le PKEK, le GEKG, le GQPR et le KTTKS indiquent que l’augmentation de la capacité de perméation de l’épiderme de ces peptides est possible et donne de bons résultats. Conclusion Bien que la capacité de perméation de la plupart des peptides antirides ne soit pas suffisamment élevée et qu’ils n’atteignent pas leurs cibles dans la peau aux bonnes concentrations, cette capacité peut être augmentée jusqu’à des concentrations thérapeutiques en recourant à diverses approches de renforcement. Chemical, physical and encapsulation approaches applied so far for enhancing the skin permeability of anti‐wrinkle peptides.